Revisión de la Literatura sobre el Problema de Programación de “Flow Shop” Híbrido con Máquinas Paralelas no Relacionadas - Peña Tibaduiza, Eliana Marcela; Garavito Hernández, Edwin Alberto; Pérez Figueredo, Luis Eduardo; Moratto Chimenty, Eslendis (Ingeniería, 2017)
Context: The flow shop hybrid problem with unrelated parallel machines has been less studied in the academia compared to the flow shop hybrid with identical processors. For this reason, there are few reports about the kind of application of this problem in industries. Method: A literature review of the state of the art on flow-shop scheduling problem was conducted by collecting and analyzing academic papers on several scientific databases. For this aim, a search query was constructed using keywords defining the problem and checking the inclusion of unrelated parallel machines in such definition; as a result, 50 papers were finally selected for this study. Results: A classification of the problem according to the characteristics of the production system was performed, also solution methods, constraints and objective functions commonly used are presented. Conclusions: An increasing trend is observed in studies of flow shop with multiple stages, but few are based on industry case-studies.